2016
DOI: 10.4103/2152-7806.181906
|View full text |Cite
|
Sign up to set email alerts
|

Epidural hematoma after routine epidural steroid injection

Abstract: Background:There are few reported cases of an epidural spinal hematoma following interventional pain procedures.Case Description:We report a case of a spinal epidural hematoma in a patient with no known risk factors (e.g. coagulopathy), who underwent an epidural steroid injection (ESI) in the same anatomic location as two previously successful ESI procedures.Conclusion:Early detection was the key to our case, and avoiding sedation allowed the patient to recognize the onset of a new neurological deficit, and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…So far, several studies reported the occurrence of epidural hematoma after spinal procedures [ 10 13 ] ; however, regarding the procedure performed through the sacral hiatus, only 1 study has reported an epidural hematoma. In 2017, Choi reported a lumbar epidural hematoma from the L2-S1 levels with concomitant central canal compromise at the L2/L3 and L3/L4 levels about 6 hours after caudal epidural steroid injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, several studies reported the occurrence of epidural hematoma after spinal procedures [ 10 13 ] ; however, regarding the procedure performed through the sacral hiatus, only 1 study has reported an epidural hematoma. In 2017, Choi reported a lumbar epidural hematoma from the L2-S1 levels with concomitant central canal compromise at the L2/L3 and L3/L4 levels about 6 hours after caudal epidural steroid injection.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural hematoma is one complication that can occur after neuraxial procedures, such as interlaminar epidural and caudal steroid injections. [ 10 13 ] The damage of neural structures from an epidural hematoma results from the expansion of the hematoma within the enclosed space of the spinal canal and can be devastating if early decompression is not performed. [ 14 ] Anticoagulation with heparin and warfarin is known to be one of the most important risk factors for epidural hematoma after neuraxial procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Such hematomas can gradually increase in size and cause compression to the neural structures and subsequent onset of weakness and decreased sensation, which can impede driving and increase risk both to the patient and others in close proximity. While the onset of sensorimotor impairment due to a developing epidural hematoma may occur within minutes [23,24] or take more than a day [25][26][27][28][29][30][31][32], there are case reports of onset in the time-frame of discharge after injection in a typical clinic setting (i.e. 20-30 minutes) [33,34].…”
Section: Sensorimotor Impairmentmentioning
confidence: 99%
“…And, while we might assume that an EH occurs at the site of a neuraxial needle puncture or catheter insertion, there is at least one report of a distant thoracic bleed occurring contemporaneous to a lumbar epidural steroid injection in a patient with no apparent risk factors besides spinal stenosis (19). A major conundrum occurs when an EH appears spontaneously, albeit contemporaneously, in a patient not on anticoagulation therapy (20,21), or in one who formerly used drugs like clopidogrel but who stopped it within the suggested timing framework promoted by the major societies of regional anesthesia and pain management (22). Do these outliers change the way we proceed in the face of former use of these drugs, or do we consider these conditions to be random chance events?…”
Section: Epidural Hematoma Formation Following Neuraxial Interventional Pain Management Procedures Have We Even Begun To Comprehend the Mmentioning
confidence: 99%